Florida Marine Baitfish Aquaculture - Marketing Opportunities and Challenges (Part 1 of a Marine Baitfish Aquaculture Series) - Marissa Drake; Andrew Ropicki; Matthew A. DiMaggio; Kelly Grogan; Courtney L. Ohs; Laura Tiu; Edward V. Camp; Jordan Moor (EDIS, 2023)
This publication, Part 1 in the Florida Marine Baitfish Aquaculture series, outlines opportunities and challenges associated with marketing aquacultured live marine baitfish in Florida. It examines why Florida is uniquely suited for the continued development of this industry, reviews the marine recreational angling baitfish market, and describes the opportunities and challenges associated with marine baitfish marketing and selling live baitfish to marine baitfish retailers. This publication is intended to provide information to current and potential farmers, as well as management agency and outreach personnel and the interested public. It should help farmers, potential farmers, and perhaps investors understand the potential scale, opportunities, and challenges of live baitfish aquaculture in Florida. This same information can assist policymakers and outreach personnel in their management decisions and the communications of those decisions.